HPV vaccine awareness, knowledge and information sources among youth in Switzerland: a mixed methods study. Issue 1 (31st January 2022) - Schwendener, Corina L; Kiener, Laura M; Jafflin, Kristen; Rouached, Sarah; Juillerat, Anna; Meier, Vincent; Schärli Maurer, Susanna; Muggli, Franco; Gültekin, Nejla; Baumann, Aron; Debergh, Marlyse; Gruillot, Catherine; et al.
Abstract : Objectives: We aimed to provide a detailed characterisation of human papillomavirus (HPV) vaccine awareness, knowledge and information sources in the HPV vaccine decision-making process of youth, both male and female, in Switzerland. Design: With a mixed-method study design, we conducted quantitative questionnaires and qualitative interviews, which lasted 20–45 min. Setting and participants: We recruited participants, 15–26 years of age, in physicians' offices, in a local sexual health clinic, and during military enlistment. We administered quantitative questionnaires to 997 youth participants (585 male, 412 female) and conducted qualitative interviews with 31 youth (17 male, 14 female). Primary and secondary outcome measures: We assessed HPV vaccine awareness, knowledge, information sources and vaccination status. Results: In the study's quantitative component, 108 (20%) male and 262 (65%) female participants had received ≥1 dose of HPV vaccine. 697 (70%) participants were knowledgeable about the HPV vaccine. Females were more likely to be knowledgeable than males (342/412 (83%) vs 355/585 (61%); p<0.01). Younger participants in the sample compared with older participants were more likely to be aware of HPV vaccine (135/148 (91%) vs 695/849 (82%); p<0.01). The three most mentioned information sources were school health programmes (442 (53%)), healthcare providers (190 (23%)) and participants' social networks (163 (20%)). Overall, 554/710 (78%) participants had a female-gendered perception of HPV vaccine, a finding which was further supported and explained by qualitative data. Conclusions: Despite a male HPV vaccine recommendation being made >4 years prior to the data collection, HPV vaccine knowledge was higher among females than males, and a female-gendered perception of HPV vaccine remains prevalent. Internet and social media were minor HPV vaccine information sources. Study findings demonstrate that HPV knowledge matters for HPV vaccine uptake and suggest that we should improve HPV information quality and access for youth, particularly by tailoring knowledge campaigns to young men.